Process sequence development for automated progressive freeze concentration system - Safiei, Nor Zanariah (Penerbit UTM Press, 2014)
Nowadays there is a growing interest on Progressive Freeze Concentration (PFC) in solution concentration process due to its several significant advantages. The PFC process is proven to be able to be applied successfully in industrial application. PFC often exhibits a dynamic character and involves complex behavior and process. Even a slight change in the operating condition can cause unstable process behavior and lead to low performance of the system. Due to these reasons, the objective of this paper is to develop a sequence for conducting PFC process. In order to develop the process sequence, it has been divided into four major steps which are feeding process, crystallization process, Product 1 collection and Product 2 collection. This system offers improved overall performance in conducting experiments as well as increased efficiency of the separation process.